PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN BERBASIS AUGMENTED REALITY (AR) PADA KELAS VII DI SMP SWASTA ALWASLIYAH PINANG BARIS - Pranata, Dwi Agus; Jamaludin, Jamaludin; Yunita, Sri (Majalah Ilmiah METHODA, 2023)
This learning is considered very boring because this learning always uses the lecture method without any learning improvisation that can increase students' desire to learn. This education aims to see how students respond and their learning level using the augmented reality method. The method used in this research is a qualitative method where the researcher gives pretest questions before the learning is implemented and a post-test after the learning is implemented to see the participants' knowledge increase. educate. It turns out that augmented reality-based learning can increase students' knowledge and students understand more about the implementation of Pancasila values both in everyday life in society and in school life.